In vitro Dissolution Testing and Pharmacokinetic Studies of Silymarin Solid Dispersion After Oral Administration to Healthy Pigs - Xu, Ying; Li, Jie; He, Bing; Feng, Tingsong; Liang, Lijie; Huang, Xianhui (Frontiers in Veterinary Science, 2022)
We evaluated the pharmacokinetics of silymarin solid dispersion in pigs to determine whether silybin bioavailability would be increased over that of a silymarin premix. In vitro dissolution testing was conducted using dissolution apparatus 1 (baskets) at 100 rpm at 37 ± 0.5°C in pH 1.2 HCl, pH 6.8 phosphate, and pH 4.3 acetate buffers containing 0.5% Tween-80. In vivo pharmacokinetics were studied using 16 healthy pigs (Yorkshire × Landrace) that were randomly assigned to two groups. Silymarin as solid dispersion and premix dosage forms were administered directly by stomach tubes at 50 mg kg−1 silybin. In vitro dissolution of silybin for the premix was 35.02, 35.90, and 38.70% in these buffers, respectively. In contrast, silybin dissolution in solid dispersions was increased to 82.92, 87.48, and 99.70%, respectively. Silymarin solid dispersion administered at a single dose resulted in a peak concentration (Cmax) of 1,190.02 ± 246.97 ng ml−1 with the area under the curve (AUC0−∞) at 1,299.19 ± 67.61 ng ml−1 h. These parameters for the premix groups were 411.35 ± 84.92 ng ml−1 and 586.82 ± 180.99 ng ml−1 h, respectively. The Cmax and AUC0−∞ values for the solid dispersion were about twice that of the premix and were consistent with the in vitro dissolution data.